Resveratrol Ameliorates Cardiac Remodeling in a Murine Model of Heart Failure With Preserved Ejection Fraction - Zhang, Liyun; Chen, Juan; Yan, Lianhua; He, Qin; Xie, Han; Chen, Manhua (Frontiers in Pharmacology, 2021)
Objective: Accumulating evidence suggested that resveratrol (RES) could protect against adverse cardiac remodeling induced by several cardiovascular diseases. However, the role of RES in the setting of heart failure with preserved ejection fraction (HFpEF) and the underlying mechanisms of its action remain understood. This study was to determine whether RES could ameliorate HFpEF-induced cardiac remodeling and its mechanisms. Methods:In vivo, C57BL/6 mice served as either the sham or the HFpEF model. The HFpEF mice model was induced by uninephrectomy surgery and d-aldosterone infusion. RES (10 mg/kg/day, ig) or saline was administered to the mice for four weeks. In vitro, transforming growth factor β1 (TGF-β1) was used to stimulate neonatal rat cardiac fibroblasts (CFs) and Ex-527 was used to inhibit sirtuin 1 (Sirt1) in CFs. Echocardiography, hemodynamics, western blotting, quantitative real-time PCR, histological analysis, immunofluorescence, and ELISA kits were used to evaluate cardiac remodeling induced by HFpEF. Sirt1 and Smad3 expressions were measured to explore the underlying mechanisms of RES. Results: HFpEF mice developed left ventricular hypertrophy, preserved ejection fraction, diastolic dysfunction, and pulmonary congestion. Moreover, HFpEF mice showed increased infiltration of neutrophils and macrophages into the heart, including increased interleukin (IL)-1β, IL-6, and TNF-α. We also observed elevated M1 macrophages and decreased M2 macrophages, which were exhibited by increased mRNA expression of M1 markers (iNOS, CD86, and CD80) and decreased mRNA expression of M2 markers (Arg1, CD163, and CD206) in HFpEF hearts. Moreover, HFpEF hearts showed increased levels of intracellular reactive oxygen species (ROS). Importantly, HFpEF mice depicted increased collagen-I and -III and TGF-β mRNA expressions and decreased protein expression of phosphorylated endothelial nitric-oxide synthase (p-eNOS). Results of western blot revealed that the activated TGF-β/Smad3 signaling pathway mediated HFpEF-induced cardiac remodeling. As expected, this HFpEF-induced cardiac remodeling was reversed when treated with RES. RES significantly decreased Smad3 acetylation and inhibited Smad3 transcriptional activity induced by HFpEF via activating Sirt1. Inhibited Sirt1 with Ex-527 increased Smad3 acetylation, enhanced Smad3 transcriptional activity, and offset the protective effect of RES on TGF-β–induced cardiac fibroblast–myofibroblast transformation in CFs. Conclusion: Our results suggested that RES exerts a protective action against HFpEF-induced adverse cardiac remodeling by decreasing Smad3 acetylation and transcriptional activity via activating Sirt1. RES is expected to be a novel therapy option for HFpEF patients.